2018
DOI: 10.1021/acs.molpharmaceut.8b00152
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Development of Novel PSMA-Targeting Radioligands: Modulation of Albumin-Binding Properties To Improve Prostate Cancer Therapy

Abstract: The treatment of metastatic castration-resistant prostate cancer (mCRPC) remains challenging with current treatment options. The development of more effective therapies is, therefore, urgently needed. Targeted radionuclide therapy with prostate-specific membrane antigen (PSMA)-targeting ligands has revealed promising clinical results. In an effort to optimize this concept, it was the aim of this study to design and investigate PSMA ligands comprising different types of albumin binders. PSMA-ALB-53 and PSMA-ALB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
210
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 111 publications
(234 citation statements)
references
References 26 publications
17
210
7
Order By: Relevance
“…Radiolysis induced by free radicals can be prevented by radioprotectants, such as ascorbic acid, human serum albumin, cysteamine and glycerol. 42,43 Figure S4), which are in agreement with other studies that have examined the binding of PSMA ligands to PSMA-positive cells. [44][45][46] Gourni et al showed that [ 11 In]In-PSMA-617 to LNCaP cells yielded a k d of 5.4 nM.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Radiolysis induced by free radicals can be prevented by radioprotectants, such as ascorbic acid, human serum albumin, cysteamine and glycerol. 42,43 Figure S4), which are in agreement with other studies that have examined the binding of PSMA ligands to PSMA-positive cells. [44][45][46] Gourni et al showed that [ 11 In]In-PSMA-617 to LNCaP cells yielded a k d of 5.4 nM.…”
Section: Discussionsupporting
confidence: 91%
“…Radiolysed radioligands have reduced receptor affinity, and, therefore, will lead to decreased therapeutic and diagnostic efficacy, and circulation in the body with increased radiation toxicity to organs such as liver and bone marrow. Radiolysis induced by free radicals can be prevented by radioprotectants, such as ascorbic acid, human serum albumin, cysteamine and glycerol …”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…With this in mind, we have focused our efforts on maximizing the therapeutic window of these powerful radiopharmaceuticals. Our choice of RPS-074 for preclinical therapy studies follows the identification of the recently reported analog RPS-072 (16), which showed dramatically reduced kidney uptake and substantially increased and prolonged tumor uptake relative to several novel PSMA-targeting ligands, including PSMA-617, RPS-063 (23), CTT1403 (24), PSMA-Alb-02 (19), and PSMA-Alb-56 (25). Although the DOTA-containing RPS-072 also chelates 225 Ac 31 , radiolabeling yield was only 49%, and the 225 Ac-DOTA complex has been found to have suboptimal in vivo stability (26,27).…”
Section: Discussionmentioning
confidence: 99%